Surgical treatment of paraspinal schwannoma of left supraclavicular fossa: a case report - ZHANG,Hai (2022)
Abstract The incidence of paraspinal schwannoma of supraclavicular fossa is low, and its operative plan and complications have not been systematic reported. Here, we reported a case of supraclavicular paraspinal schwannoma in our center. The operative methods, intraoperative precautions and postoperative complications were illustrated. A 54 years old male patient was admitted to hospital due to pain in the left chest and back for 20 days. MRI showed 32 × 68 × 38 mm tumor adjacent to the spine of the left supraclavicular fossa. The patient underwent supraclavicular incision surgery, and the postoperative pathology showed schwannoma. After the operation, the nerve of the left upper limb was damaged, which was manifested as numbness in the skin above the joint of the left thumb, left index finger, middle finger, ring finger and little finger. The skin above the second finger joint of the little finger is numb and the grip strength is weakened. One month after operation, the symptoms were relieved. Surgery is the first choice for the treatment of supraclavicular tumors. It is necessary to review the anatomy of supraclavicular region in detail before the operation, and to protect important nerves and vessels during the operation.